Analisis Pendekatan Deep Learning Sebagai Upaya Endorsment Pendidikan: Penelitian - Agussabeth Adelina Pasaribu; Tri Indah Prasasti; Sri Ulina Br Sembiring; Angelnia Br Bukit; Eskawana Nababan; L. Lutfiah; Yana Melia Sari Sipayung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the deep learning approach as an effort to strengthen the image of education (endorsement). The method used is a literature study, by collecting and analyzing various sources of basic academic data such as Google Scholar and others. The results of the study indicate that deep learning has revolutionary potential in education, not only to predict student performance, but also to understand the complex factors that influence learning success. The application of deep learning can also improve the image of educational institutions by giving the impression of being innovative and in tune with current developments. However, there are challenges such as inequality of access, teacher readiness, ethical issues and data privacy, and the potential decline of the role of teachers. This study also highlights the importance of integrating the Independent Curriculum and the deep learning approach to improve the quality of education in Indonesia. The study results show that the deep learning approach can improve learning outcomes and student interest because learning is not monotonous, involves students in critical thinking, and learning with creativity and innovation. However, careful planning is required before implementation.